2005
DOI: 10.1016/j.drugalcdep.2004.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of d-amphetamine in human models of information processing and inhibitory control

Abstract: Although stimulants are generally associated with enhanced information processing, reports of stimulant effects on behavioral functions that rely on inhibitory processes have been inconsistent. The present research tested the joint effects of d-amphetamine on information processing and inhibitory control in healthy adults (N = 22) with no reported history of illicit stimulant use or drug dependence. Information processing was measured by a rapid information processing (RIP) task and inhibitory control was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…Similarly, single doses of cocaine reduced the ability to inhibit responses of cocaine abusers in a stop-signal task (Fillmore et al, 2002). It has been suggested that repeated dopaminergic stimulation of prefrontal pathways leads to impairment of inhibitory functions (Volkow et al, 1997a, b) and that neural changes following chronic stimulant use may alter the behavioral response to acute dopaminergic stimulation (Fillmore et al, 2005). In the present study, the subjects can be best qualified as light-to-moderate MDMA users.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, single doses of cocaine reduced the ability to inhibit responses of cocaine abusers in a stop-signal task (Fillmore et al, 2002). It has been suggested that repeated dopaminergic stimulation of prefrontal pathways leads to impairment of inhibitory functions (Volkow et al, 1997a, b) and that neural changes following chronic stimulant use may alter the behavioral response to acute dopaminergic stimulation (Fillmore et al, 2005). In the present study, the subjects can be best qualified as light-to-moderate MDMA users.…”
Section: Discussionmentioning
confidence: 65%
“…Rats with dorsomedial striatal lesions with impaired SSRTs compared with control subjects had significantly improved SSRTs following D-amphetamine treatment, whereas control subjects showed little response to the drug (Eagle and Robbins 2003a). Indeed, studies that have found little effect of stimulant drugs on SSRT have usually only considered the population as a whole (Fillmore et al 2005). The clear benefit of using normal variation within a population to investigate disorders such as ADHD is that symptoms of these disorders can be modelled whilst making no assumptions about their underlying pathology, unlike other potential 'models' of ADHD.…”
Section: Evidence For Baseline Dependence Of Psychostimulant Actionmentioning
confidence: 99%
“…Participants completed a 5-min computerized version of the RIP (Fillmore et al 2005). Information processing capacity (working memory) was determined based on the rate of digit presentation maintained and signal detection accuracy (proportion of hits) during this self-paced task.…”
Section: Rapid Information Processing Task (Rip)mentioning
confidence: 99%
“…Participants completed a 7.75-min computerized version of the stop-signal task (Fillmore et al 2005). Inhibitory control was determined by examining reaction time and duration of the delay between go and stop signals that could effectively inhibit cued responding.…”
Section: Stop-signal Taskmentioning
confidence: 99%